Lime-scavenged reduction of molybdenite - Prasad P.M.; Mankhand T.R.; Rao P.S. (My University, 2025)
Of the numerous approaches proposed during the past two decades for molybdenum extraction, a new route of considerable promise is the direct reduction of molybdenite in the presence of the potent sulphur scavenger lime. This paper presents an overview of the researches carried out on this subject in our laboratory. Thermochemical aspects relevant to the lime-enhanced reduction of MoS2 by H2, CO and C are discussed. Studies on the direct reduction of a high-grade molybdenite concentrate by H2 or CO reveal that CaO addition enhances the reduction rates up to two orders of magnitude and reduces sulphur emission into off-gas to very low levels. Whereas direct carbothermy of MoS2 has not been detected, lime addition makes it highly feasible. XRD studies on reacted products indicate, besides molybdenum metal, the intermediate formation of CaMoO4 and/or Mo2C. The lime-scavenged reduction of molybdenite is a complex process involving a number of successive and parallel reactions. A sulphur-oxygen exchange reaction in which CaMoO4 is the intermediate product is proposed to be the pre-requisite reaction. For production of high-purity molybdenum, lime-hydrogen reduction of molybdenite is suggested whereas molycarbide can be made by carbon monoxide reduction. Relative merits of the three reducing agents and the technological potential of the new approach have also been discussed. © 1993.